Multiple orogenic gold mineralization events in a collisional orogen: Insights from an extruded terrane along the southeastern margin of the Tibetan Plateau. (June 2021) - Yang, Lin; Wang, Qingfei; Groves, David I.; Lu, Song; Li, Huajian; Wang, Peng; Deng, Jun
Abstract: The Daping and Chang'an orogenic gold deposits in the extruded Jinping terrane of the Cenozoic Ailaoshan collisional orogen, on the southeastern margin of the Tibetan Plateau, provide an opportunity to study relationships between the geodynamic evolution of a collisional orogen and orogenic gold mineralization. The Daping gold deposit comprises NW−SE-trending gold lodes hosted by ductile-brittle, dextral-reverse shear zones that developed under sub-horizontal NNE−SSW-oriented compression. In contrast, the Chang'an gold deposit comprises disseminated ores controlled by NW-trending brittle, sinistral strike-slip faults that formed under sub-horizontal NW−SE-oriented compression. Reliable Ar−Ar dating of two gold-related hydrothermal sericites at Daping constrain mineralization to ca. 46−42 Ma, whereas ca. 35 Ma gold-mineralized syenites, the inferred stress field, and published paleomagnetic evidence suggest that the Chang'an deposit formed later at ~23−21 Ma. These different mineralization ages, together with contrasting sulfur isotope compositions of gold-related sulfides at Daping and Chang'an, indicate that the Daping deposit formed in the northwestern part of the Ailaoshan orogen during crustal thickening before extrusion of the Jinping terrane, whereas the Chang'an deposit formed to the southeast at a late stage of terrane extrusion. From this rare window into a gold-mineralized Cenozoic orogen, it can be demonstrated that at least two periods of orogenic gold mineralization occurred at evolving stages of the geodynamic evolution of the collisional orogen. Highlights: Multistage orogenic gold events within evolving Cenozoic collisional orogen. Extruded Jinping terrane hosts tectonically juxtaposed orogenic deposits. Deep-crust Daping deposit hosted by dextral-reverse shear zones. Shallow-crust Chang'an deposit hosted by sinistral strike-slip faults.